Pemikiran Muhammad Quraish Shihab Tentang Nikah Siri - Muhammad Abdul Basir; Nurul Ainun Azisah; Elisa Rani; Muh Fasral Hafid; Nurhikma; Muhammad Fatur Anggara; Eko Nursalim (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
Quraish Shihab revealed a pattern of unregistered marriages, namely that marriages are not approved by religion, nor are they sanctioned by the marriage law. In addition, the Prophet advised those who were married to have a walimah party, even if they only invited a certain number of people for a meal of one goat. He is an Indonesian cleric whose thinking tends  to  be  in  the  field  of  interpretation  and knowledge  of  the  Al-Qur'an.  However,  in  its  development,  M. Quraish Shihab began to enter the realm of Islamic law by answering Islamic legal problems and was then published by a publisher with the character al-as'ilah wa al-answer. In researching M, Quraish Shihab,  the  author  conducted  library research  in  the  form  of  his works using a content analysis approach, namely trying to understand and analyze data related to unregistered marriages, with this approach the author hopes to find a conclusion about thoughts M. Quraish Shihab. M. Quraish Shihab is of the opinion that a marriage without a registered marriage can result in a sin for the perpetrator because it violates the provisions set by the government and the DPR (Ulil Amri). He took the legal basis regarding sirri  marriage by using contextualization of school of thought thinking, and using the qiyas method in Surah Al-Baqarah, the rules of Islamic fiqh sad az-zari'ah, as well as KHI and Marriage Law No. 1 of 1974. This research is qualitative research, namely descriptive-analytic library research. The author collects information through reading books and other primary and secondary materials relevant to the research topic. The author adopts normative juridical methodology in this research.